2014
DOI: 10.1093/mutage/geu001
|View full text |Cite
|
Sign up to set email alerts
|

A potentially functional polymorphism in the promoter region of miR-34b/c is associated with renal cell cancer risk in a Chinese population

Abstract: Members of the miR-34 family have been shown to be transcriptional targets of the tumour suppressor gene P53. Aberration expression of miR-34 impairs p53-mediated cell cycle arrest and apoptosis. A single nucleotide polymorphism T > C (rs4938723) located within the CpG island in the promoter region of pri-miR-34b/c may affect its expression and has been suggested to influence cancer risk. In this study, we genotyped rs4938723 using the TaqMan method to explore the relationship between this polymorphism and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Pan et al (27) reported that the CT and CT/CC genotypes of the miR-34b/c rs4938723 were associated with a significantly decreased risk of gastric cancer compared with the TT genotype. It has been shown that the pri-miR-34b/c rs4938723 C allele may increase the susceptibility to renal cell carcinoma by decreasing the activity of pri-miR-34b/c promoter (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pan et al (27) reported that the CT and CT/CC genotypes of the miR-34b/c rs4938723 were associated with a significantly decreased risk of gastric cancer compared with the TT genotype. It has been shown that the pri-miR-34b/c rs4938723 C allele may increase the susceptibility to renal cell carcinoma by decreasing the activity of pri-miR-34b/c promoter (30).…”
Section: Discussionmentioning
confidence: 99%
“…miR-34a is encoded by its own transcript, while miR-34b and miR-34c share a common primary transcript (pri-miR-34b/c) (9). The promoter region of miR-34b/c transcripts contains p53-binding sites (22 Numerous studies investigated the impact of miR-34b/c rs4938723 on the risk of various cancers, but the results are inconsistent (19,(23)(24)(25)(26)(27)(28)(29)(30)(31). To the best of our knowledge, there is only one previous study regarding the impact of the miR-34b/c variant on BC risk (32).…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance to the known role of both genes in cancer-related pathways. For example, MIR-124A is correlated with breast cancer growth and aggressiveness (86), whilst MIR-34B, which has tumor-suppressive effects through the inhibition of BCL-2 (87), is associated to renal cell cancer risk (88) and silenced in hepatocellular carcinoma (89). …”
Section: Discussionmentioning
confidence: 99%
“…GATA-X transcription factors can activate or repress expression of target genes when they bind to a specific DNA sequence (A/T) GATA (A/G) in the region of promoters (Bossard et al, 1998). In recent years, some case-control studies have been conducted to determine the association between rs4938723 and multiple kinds of cancers in various types, such as hepatocellular carcinoma (Xu et al, 2011;Han et al, 2013;Son et al, 2013), colorectal cancer (Gao et al, 2013;Oh et al, 2014), renal cell cancer (Zhang et al, 2014), esophageal cancer (Yin et al, 2013), nasopharyngeal carcinoma and breast cancer (Bensen et al, 2013). However, the results are conflicting and inconclusive.…”
Section: Research Articlementioning
confidence: 99%